Use of bioengineering techniques in river restoration from a functional perspective: understanding drivers of nitrogen removal - Ribot, Miquel (2016)
Many bioengineering techniques involve the use of helophytes to reduce soil erosion and increase landscape stabilization. However, helophytes can influence carbon (C) quality, water residence time and biogeochemical rates, and thus they can also play a relevant role on in-stream nitrogen (N) removal (Peipoch et al., 2013). Therefore, these bioengineering techniques could be successfully applied in stream reaches downstream of wastewater treatment plant (WWTP) effluents which usually exhibit a high capacity to nitrify ammonium but a low capacity to permanently remove N via denitrification (Ribot et al. 2012). In this study, we tested the effect of helophytes on net N removal by using flumes receiving treated water from a WWTP. Furthermore, we added a labile C source to the flumes to test whether the low C quality of the treated waste water can limit N removal, and in particular denitrification.